Enhanced electromagnetic wave absorption properties of PDCs-SiCN(Ni) fibers by in-situ formed CNTs and Ni2Si. Issue 14 (15th July 2022) - Guo, Xue; Lu, Junbin; Liu, Jie; Liu, Chunmiao; Tong, Yanchun; Li, Jiao; Sun, Haibin; Peng, Hui; Wu, Shigang; Feng, Yurun; Gong, Hongyu
Abstract: By utilizing polymer-derived ceramics (PDCs) method and electrospinning technology, SiCN(Ni) fibers with 1 wt% nickel content at different calcination temperatures (1000–1300 °C) were synthesized. The properties of PDCs-SiCN(Ni) fibers were tested by XRD, SEM, TEM, Raman spectroscopy, XPS and vector network analyzer. The results showed that the addition of nickel acetylacetonate (NA) promoted the in-situ formation of CNTs and Ni2 Si at high temperatures, which could adjust the impedance matching performance and improve the electromagnetic wave (EMW) absorption properties. The minimum reflection loss (RL) of SiCN(Ni) fibers was −47.55 dB (4.2 mm), and the effective absorption band (EAB, RL ≤ −10 dB) was 3.6 GHz (14.4–18 GHz) under the ultra-thin thickness of 1.24 mm.